The Model of Innovative Challenges with the Approach of Responding to Industrial Demands - Hosseini, Hadi; Azad, Naser; Modiri, Mahmoud; Mantegi, Manochehr (AI and Tech in Behavioral and Social Sciences, 2024)
AbstractPurpose: In today’s competitive markets, innovation is essential for survival and success. Companies adopt various tools to foster innovation and address their challenges—one of which is hosting innovative challenges. These events allow firms to engage with problem-solving communities to generate solutions. This study aims to explore the conditions necessary for organizing such events and to identify the key factors that influence their success in addressing industrial demands.Method: This research employs a mixed-methods approach (qualitative–quantitative). Initially, a qualitative method was used to extract relevant factors from existing literature through content analysis, expert interviews, and open coding. Subsequently, the identified factors were screened using a quantitative approach, specifically the fuzzy Delphi method, conducted in two rounds with expert input. To develop a conceptual model comprising indices and sub-indices, exploratory factor analysis was conducted based on expert evaluations. Finally, the proposed model was validated through confirmatory factor analysis using structural equation modeling in LISREL software.Findings: The results indicate that the process of conducting innovative challenges to address industrial needs consists of four main stages: Problem Definition, Information, Evaluation, and Acquisition. Additionally, 20 critical success factors were identified as essential for organizing an effective event. Based on these findings, a comprehensive model for implementing innovative challenges was developed.